THE EFFECT OF COMBINED ULTRASOUND AND MC KENZIE ON IMPROVING FUNCTIONAL ABILITY IN PATIENTS WITH MYOGENIC LOW BACK PAIN - Arief Efendi; Nurul Halimah (STAND, 2023)
Low back pain is a musculoskeletal disorder with signs of pain in the area around the lower back, the incidence is mostly myogenic low back pain, it increases with age. Physiotherapy interventions used to improve functional ability with a combination of ultrasound and mc kenzie. The purpose of this study was to determine the effect of a combination of ultrasound and mc kenzie on improving functional abilities in patients with myogenic low back pain. This research design uses a type of quasi-experimental with a one group pretest and posttest approach, this study has 20 respondents using a sampling technique, namely purposive sampling. The effect of the combination of ultrasound and mc kenzie on functional ability in myogenic low back pain patients with a p-value = 0.001 (p <0.05). Based on the results of this study, it is stated that the combination of ultrasound and mc kenzie can improve functional ability in myogenic Low Back Pain patients performed 2 times a week for 4 weeks.